A Macroprudential Framework for the Early Detection of Banking Problems in Emerging Economies - Claudio M. Loser; Miguel A. Kiguel; David Mermelstein (Asian Development Bank (ADB), 2010)
This paper develops an analytical framework that can be used to anticipate problems in the banking system and enable supervisors to take mitigating actions at an early stage. > This paper has two components. First, it develops an early warning indicator that is intended to capture a number of the systemic risks that can affect the banking system as a whole. Second, it develops a methodology to detect problems at the individual bank level in an effort to identify those firms with financial vulnerabilities. > For the systemic component of our methodology, the final output is a banking system vulnerability index to facilitate bank monitoring tasks, as well as some disaggregated subcomponents that are intended to display the relative importance of the different risks (e.g., liquidity, currency, and interest rate risks). Regarding the assessment of the soundness of individual institutions, the paper uses a methodology based on cluster analysis that incorporates the results of the previous framework. > There is an empirical application of the systemic component that is based on the 2001 Argentine banking crisis. It shows that the proposed vulnerability indicator started to increase steadily beginning in 1999, following 2 years in which it had remained flat, and it finally peaked in mid-2001, which was just before the onset of the crisis.
hdl:11540/1965
Keywords: E44; E58; E65; G21; G28; 330; Banks; stress testing; banking crises; banking regulation; banking supervision; early warning systems